(untitled) - Petros P Xanthakos (Upper Saddle River, New Jersey, 1996)
The book presents the methodologies used by states and general agencies to identify the bridge needs and prioritize projects eligible for maintenance, improvement, or replacement; reviews procedures used to assess bridge deficiencies; introduces the fundamentals of structural capacity analysis to assess the overall structure adequacy of existing bridges; identifies the usual problems and defects of bridge components; and reviews the methods and techniques used to implement repairs, strengthening, retrofiting, rehabiliting, replacement, and related improvements
Keywords: bridges - maintenance and repair,bridges - united states - maintenance and repair